Effect of a STEM module integrated with computational thinking on problem-solving skills of 5-year-old children - Ulker Hancer, Nazli; Topcu, Mustafa Sami (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2026)
BackgroundIn recent years, as a result of developments in technology, interest in holistic approaches that combine computational thinking with disciplines such as STEM in the field of education has been steadily increasing.PurposeThis study investigated integrating computational thinking skills into STEM education, particularly focusing on the effect on the problem-solving skills of early childhood children.SampleIn the study, which was based on a quasi-experimental design involving two groups (experimental: n = 16 and control: n = 17), data were collected using the Problem-Solving Skills Scale (4-7 years).Design and methodsIn the control group, the process was carried out with STEM activities prepared by the researcher. In the experimental group, on the other hand, the process was carried out with the activities included in the STEM module integrated with computational thinking, which included six sub-dimensions of computational thinking: representation, control structures, modularity, algorithms, hardware/software and debugging.ResultsAs a result of the analyses conducted, it was determined that computational thinking-integrated STEM activities caused a significant improvement in the problem-solving skills of early childhood children (p < .05). The results showed that the process of STEM activities integrated with computational thinking had a significant positive impact on early childhood children's problem-solving skills compared to the process of STEM activities only.ConclusionsThe results obtained from the study will contribute to early childhood education in the field of quality education, which is among the sustainable development goals.
Keywords: Computational thinking; early childhood; integrated; STEM; problem-solving skills; SDG 4: Quality education; Education & Educational Research